Validation of the autonomous learning strategies scale in Peruvian university students: evaluation of factorial models - Ipanaqué-Zapata, Miguel; Bazalar-Palacios, Janina; Figueroa-Quiñones, Joel; Quiñones-Negrete, Magaly; Velasquez-Castillo, Nilo Albert; Valle-Sandoval, Hessel; Rivera-Lozada, Oriana; Cayetano-Terrel, Paolo; Cerna-Salcedo, Alberto (Frontiers in Education, 2025)
Autonomous learning is a fundamental competence in higher education, empowering students to take control of their academic development. Assessing this skill reliably requires robust measurement tools. This study aimed to evaluate the factorial structure and internal consistency of the Autonomous Learning Strategies Scale (CETA) among university students in Peru. We included 418 college students from professional education programs in Peru who participated in the study. The CETA, designed to assess multiple dimensions of autonomous learning, was subjected to rigorous psychometric evaluation. First-order, second-order, and bifactor models were tested through exploratory and confirmatory factor analyses. Reliability was examined using Cronbach’s alpha and McDonald’s Omega coefficients. The second-order factor model with six underlying dimensions demonstrated the best fit indices and model stability. Inter-factor correlations were moderate and conceptually coherent with the scale’s theoretical structure. The findings support the second-order model as the most reliable and valid representation of the CETA. This model is recommended for future research and practical applications in educational settings aimed at evaluating and fostering autonomous learning in university students.